Composition and structure of the Chironomidae (Insecta: Diptera) assemblage of Ventania hill system streams (Argentina) along an altitudinal gradient - Siri, Augusto (2022)
A two-year study was conducted in a conservation area of the Ventania hill system where the Pampean grassy steppes and their headwater springs maintain conditions close to natural ones. The composition and the structure of Chironomidae (Insecta: Diptera) along two short hill pristine streams and their relationship with the physicochemical variables were analyzed. A total of 15444 individuals belonging to 37 species of four subfamilies were identified. An assemblage structure more similar to those described for Andean or Argentine extra-Andean hill streams than to those of the surrounding Pampas was observed. Orthocladiinae showed the highest and Podonominae the lowest taxonomic richness and density. Chironominae was best represented downstream by genera with wide distribution. From the five Podonominae genera reported in the Andean-Patagonic region, three of them (Podonomus Philippi, Parochlus Enderlein and Podonomopsis Brundin) were collected. The presence of Podonomus and Podonomopsis represent the reports at lower altitudes for both genera. The physicochemical variables differed between seasons, and only water conductivity showed an altitudinal gradient. Those species prevailing in piedmont sites correlated positively with conductivity. With few exceptions, the species collected were recorded in both seasons. In Toro stream, density was significantly highest in Spring of the second year. This study provides the ecological and systematic baseline knowledge of an insect group widely used in biomonitoring of aquatic environments, to provide biological information that supports the importance of preserving this area.